2005
DOI: 10.1007/s10397-005-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of adnexal masses in adolescent females: a multidisciplinary approach

Abstract: Laparoscopic surgery could be considered the gold standard in managing adnexal masses. The advantages of laparoscopic surgery have been proven in the adult population, and thus its use has been promoted for treating children and adolescents. However, although adolescent females should not be treated like children, their management differs from that of adults. We present three cases to illustrate how three adolescent girls had their adnexal masses dealt with laparoscopically. We recommend that hospitals conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…During the time of imaging examination by US scan or MRI, a trial of conservative management with strong analgesia is indicated in order to provide comfort to the patient. If pain resolves in If there is any suspicion of malignancy associated with an ovarian mass, then laparotomy should be organised in coordination with a multidisciplinary team that includes a paediatric oncologist surgeon or gynaecologist [17]. In all the other cases, diagnostic laparoscopy is the method used to confirm directly the status of the adnexa and provide the diagnosis.…”
Section: Managementmentioning
confidence: 99%
“…During the time of imaging examination by US scan or MRI, a trial of conservative management with strong analgesia is indicated in order to provide comfort to the patient. If pain resolves in If there is any suspicion of malignancy associated with an ovarian mass, then laparotomy should be organised in coordination with a multidisciplinary team that includes a paediatric oncologist surgeon or gynaecologist [17]. In all the other cases, diagnostic laparoscopy is the method used to confirm directly the status of the adnexa and provide the diagnosis.…”
Section: Managementmentioning
confidence: 99%